Two new combinations in the genus Panus (Panaceae, Polyporales) based on morphology and molecular phylogeny - N., Vinjusha; Kumar, T. K. Arun (Phytotaxa, 2021)
Panus is a genus of the order Polyporales with a gilled hymenium. Although Panus was earlier considered as a sub genus of the genus Lentinus, molecular phylogenetic studies support the independent status of the genus. As a result, many species were transferred from Lentinus to Panus. Many more species of Lentinus that are more related to Panus, still await critical taxonomic studies and formal transfers. Morphological and molecular data obtained from L. bambusinus and L. roseus reveal that these are Panus species. Two new combinations in the genus Panus are proposed here.